Assessing synergies and trade-offs between ecosystem services in forest landscape management. (December 2021) - Jafarzadeh, Ali Akbar; Mahdavi, Ali; Shamsi, Seyed Rashid Fallah; Yousefpour, Rasoul
Abstract: Human induced land use changes affect the provisioning of ecosystem services and may follow some economic rationale. Allocation of limited natural resources to different land utilization forms is the ultimate management problem for sustainable development. This study attempts to analyses the current land-use allocation systems in the Zagros area of western Iran suffering from soil erosion and water yielding problems and providing crucial economic benefits for local communities. Therefore, a comprehensive study using multiple advanced methods is needed to examine the ways land-use allocation can be enhanced with respect to multiple ecosystem services. For this, we have considered four ecosystem services, namely water yield, prevention of soil erosion, carbon sequestration and marketable products (wood, food). The economic efficiency (marketable production) of four different and competing land-uses, i.e. forest, pasture, orchard, and agriculture, were calculated applying a direct market valuation. To estimate the provision of ecosystem services, natural capital project tools InVEST and MPSIAC were used to model water production and total carbon budget (aerial biomass, underground, litter and soil), respectively. A Land-Use Conflict Identification Strategy model was used to classify Synergies and Trade-offs between the ecosystem services. A map was then developed to illustrate the spatial distribution of services, their provision levels, and to better understand trade-offs and synergies among a bundle of ecosystem services. To select sample points, a systematic random network was implemented on the map of the region and 533 sample points were selected. We used these sample points to assess the provision of ecosystem services and their synergies and trade-offs. To account for decision-makers' preferences about the ecosystem services, a non-linear programming method was used to optimize multi-objective land-use allocation by weighing multi-objective benefits from ecosystem services at the landscape level. The results showed that 75% of the studied sample points had synergies, at least between two services, and 25% of the sample points showed trade-offs between the ES. The highest synergies were achieved between water production and prevention of soil erosion. The highest maximum target function was found for a diversity of scenarios aiming for 0–100% provision of the four services. In superior options, forest area level has increased by 75% and the level of orchards has increased by 258% (Relative to the initial area before optimization). The pasture area decreased by 45% and the agricultural land-use area was 65% lower than the pre-optimal level. The erosion rate of the region was reduced about 3736 tons/ha/year relative to pre-optimized conditions (100, 514 tones/ha/year) and the water yield capacity increased by 663, 100 cubic meters in the whole area, which is of great value due to the importance of water availability in the region. In addition, 76, 905 tons /whole area have been added to the carbon storage function. Finally, 172, 597 million Rials revenue generation (80%) could be realized for the entire region of 13484 ha. Highlights: Analyzing the current land-use allocation systems in Zagros for ecosystem services. Applying a land-use conflict classification model of Synergies and Trade-offs. Analyzing the provision of water, carbon, erosion, and marketable products. Finding an integrated optimal land allocation scenario for ecosystem services.